DESIGN AND DEVELOPMENT OF T2IG APPLICATION: A NEED ANALYSIS - Mohd Hishamuddin Abdul Rahman; Punithavili Mariappan; Maran Chanthiran; Abu Bakar Ibrahim (Journal of Islamic, Social, Economics and Development, 2022)
This study aims to identify the need of developing an artificial intelligence technology educational application. This application is named T2IG, an acronym for Text to InfoGraphics. Meanwhile, the ADDIE and Text Analytics models have been applied to develop T2IG applications. The researcher selected 159 Malay language teachers from Penang state primary schools. A simple random sampling method was used to determine the number of study samples in this phase. Quantitative methods using a survey approach were carried out. The findings of the descriptive analysis indicate that teachers need the development of this educational application. A total of 10 items were listed to identify the development needs of this application. Next, an inferential analysis was conducted to identify differences in the level of T2IG application development requirements. The t-test and one-way ANOVA findings show no difference in the level of T2IG application development requirements based on demographical factors. Thus, this study can contribute to education by developing an educational application with artificial intelligence elements. Using this application, students will have technological instructional material for learning the Malay language.